The Efforts to Realize Responsive Local Regulations for Community Development - Tanti Kirana Utami (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
Each formation of local regulations must meet philosophical, sociological, and juridical elements. This aims to form local regulations that can keep up with the community developments and can be applied effectively. The problems under the study were the requirements and efforts related to responsive local regulations. The study employed a normative-juridical approach. Specifically, This study used descriptive-analytical research. The findings revealed the local regulations must have clear philosophical, sociological, and juridical values to create a responsive regulation to community development. In addition, this study also concluded that this matter also gave the community an opportunity to take part in forming local regulations. Meanwhile, the efforts can also be done by establishing local regulations based on applicable laws and regulations. Besides, this should also be accompanied by academic texts and public hearing to gather public opinion on the discussion of draft local regulations